2019
DOI: 10.1371/journal.pntd.0007946
|View full text |Cite
|
Sign up to set email alerts
|

Nested PCR and the TaqMan SNP Genotyping Assay enhanced the sensitivity of drug resistance testing of Mycobacterium leprae using clinical specimens of leprosy patients

Abstract: BackgroundAlthough leprosy is efficiently treated by multidrug therapy, resistance to first-line (dapsone, rifampin) and second-line (fluoroquinolones) drugs has been described worldwide. However, the characteristics of drug resistance in Southwest China remain unknown. Furthermore, the sensitivity of polymerase chain reaction (PCR)/sequencing for resistance detection is limited, especially for paucibacillary (PB) leprosy patients. The current study aimed to develop a nested PCR/sequencing and TaqMan SNP Genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Recent studies in China (5), France (6), and India (7) reported AMR proportions of 25%, 11.2%, and 7% among leprosy isolates, respectively. Despite these reports, it is still unknown whether AMR affects the maintenance of disease burden.…”
mentioning
confidence: 99%
“…Recent studies in China (5), France (6), and India (7) reported AMR proportions of 25%, 11.2%, and 7% among leprosy isolates, respectively. Despite these reports, it is still unknown whether AMR affects the maintenance of disease burden.…”
mentioning
confidence: 99%
“…(#3) Treatment: Drug resistance is an important consideration in treating leprosy. According to the recommendations of the World Health Organization, multi-drug therapy was adopted as the main treatment for leprosy (Rifampicin, Aminophenazone, and Clofazimine) [ 37 , 38 , 39 ]. However, there have been increasing reports of drug-resistant strains of Mycobacterium leprae, and the local drug-resistance rate has reached 8%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and 95% CI of the drug−resistance rate for each study are represented. Forest plot of drug−resistance rates of Mycobacterium leprae isolates in studies meeting inclusion criteria (n = 25) [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Figurementioning
confidence: 99%